2020
DOI: 10.3390/nu12072033
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Vitamin D Supplementation on Inflammatory Markers in Non-Obese Lebanese Patients with Type 2 Diabetes: A Randomized Controlled Trial

Abstract: Background: A low serum 25-hydroxyvitamin D (25(OH) D) concentration has been associated with a higher risk of type 2 diabetes mellitus (T2DM), especially in older people. Our aim in this randomized controlled trial was to evaluate the effect of vitamin D treatment on inflammatory markers in non-obese Lebanese patients with T2DM, living in Beirut, Lebanon. Methods: Non-Obese patients with T2DM (n = 88), deficient/insufficient in vitamin D, were randomly assigned into one of two groups—a treatment group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 49 publications
0
33
1
Order By: Relevance
“…However, recent findings from randomized placebo trial data by Urbain et al, 2011 shows that button mushroom treated with UV-B can improve vitamin D2 bioavailability among human subjects, and the significant value does not differ with vitamin D2 supplements [96]. In addition, studies by Wenclewska et al, 2019;Mutt et al, 2020;Hajj et al, 2020;and Cojic et al, 2021 demonstrated the positive impact of vitamin D supplementation (2000IU and 30,000IU) on T2DM, which requires further trials [97][98][99][100]. Therefore, the question remains the exact mechanism and dose-dependent action of vitamin D on diabetes mellitus treatment.…”
Section: Role Of Vitamin D In Blood Glucose Regulationsmentioning
confidence: 99%
“…However, recent findings from randomized placebo trial data by Urbain et al, 2011 shows that button mushroom treated with UV-B can improve vitamin D2 bioavailability among human subjects, and the significant value does not differ with vitamin D2 supplements [96]. In addition, studies by Wenclewska et al, 2019;Mutt et al, 2020;Hajj et al, 2020;and Cojic et al, 2021 demonstrated the positive impact of vitamin D supplementation (2000IU and 30,000IU) on T2DM, which requires further trials [97][98][99][100]. Therefore, the question remains the exact mechanism and dose-dependent action of vitamin D on diabetes mellitus treatment.…”
Section: Role Of Vitamin D In Blood Glucose Regulationsmentioning
confidence: 99%
“…Two reviewers exactly screened documents by title and abstract, and 2011 records were excluded from the process. Finally, from 168 full texts, 12 eligible trials [ 13 , 30 40 ] were selected for the systematic review and meta-analysis (Fig. 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…The studies were published between 2010 and 2020. Ten of included studies have been designed as RCT [ 31 40 ] and ones as non-RCT [ 30 ], and Verrusio et al [ 13 ] designed their study as a before-after experiment, so it was not analyzed in the meta-analysis. Six studies were conducted in the European countries [ 13 , 30 , 32 , 33 , 36 , 38 ], two in Lebanon [ 39 , 42 ], and four enrolled in other countries.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has also a role in glucose homeostasis and sensitivity to insulin. 9 In addition, recent work has shown that patients diagnosed with vitamin D deficiency (serum level of [25(OH)D] below 20 ng/ml) had a higher prevalence of DN than those who were diagnosed with insufficiency (20 -30 ng/ml) or sufficiency (30 to 60 ng/ml). 8,10,11 Moreover, many studies suggest the use of vitamin D supplementation could improve the symptoms of DN.…”
Section: Introductionmentioning
confidence: 99%